Reducing anxiety in first-stage laboring mothers with murottal music therapy and natural sound therapy - Mujahidah, Sa'adah; Rini, S; Mayangsari, Dewi; Sulistiyowati, Dwi (Link Journal of Mental Health, 2024)
Introduction: Normal labour refers to the spontaneous birth of a single, term foetus, occurring between 4 to 24 hours, without the need of interventions, and often induces minimal anxiety in mothers during the labour process. One of the anxiety treatments encompasses Murottal Music Therapy and Natural Sound Therapy. Administering Murottal Music Therapy and Natural Sound Therapy to moms experiencing anxiety helps alleviate anxiety levels during labor, facilitating a smoother and more normal procedure. Objectives: The objective of the study is to assess the efficacy of mutual music therapy and natural sound therapy on anxiety levels in mothers during the active phase of labor at Wonokerto I Health Centre. Methods: Quasi-experimental research design utilizing a pretest-posttest control group with a sample of 32 laboring women selected by purposive sampling. The independent variables are mutual music treatment and natural sound therapy, while the dependent variable is the anxiety level in laboring moms. Administering treatment to nervous moms, followed by the observation of anxiety levels in both the intervention and control groups. Results: Statistical analysis utilizing the Independent T-Test revealed a significant p-value of 0.045, less than the alpha level of 0.05. Conclusion: This indicates the effectiveness of mutual music therapy and natural sound therapy on anxiety levels in laboring mothers during the active phase, with a P value of 0.045.